Designing of 3D printed bone scaffold using Hydroxyapatite-Polylactic Acid (HA-PLA) composite - Castillo, Patrick Aldwin C.
Three-dimensional (3D) printing has been garnering interest for the past few years for its applications in the field of research and manufacturing industry. This method has a huge potential for biomedical industry, specifically in the production of bone scaffolds for treatment of osteoporosis and other bone related injuries. This technique allows fabrication of cost effective, structurally sound, and dimensionally accurate bone scaffolds. This study aims to design and produce a mechanically sound and bioactive bone scaffold using 3D printing. To determine the most suitable material for the bone scaffold, an initial material selection technique called analytical hierarchical process (AHP) was utilized. From the analysis, it was selected that a biocomposite made from hydroxyapatite (HA) and polylactic acid (PLA) is ideal for the said application. The HA-PLA composites were prepared as filaments via single screw extruder. These filaments were then used as feed materials for the fused filament 3D printer. Fourier transform infrared spectroscopy results confirmed the fabrication of a HA-PLA composite. The thermal properties were measured using thermogravimetric analysis and differential scanning calorimetry. Results of these measurements showed the relative homogeneity of the produced 10wt%HA: 90wt%PLA filaments, and its melting point was found to be 148.67°C, which is lower than pure PLA (2 10°C). The compressive mechanical tests of the samples showed that the modulus, offset yield strength, and strength at 20% strain decreases as the hydroxyapatite content increases. Two designs, specifically aligned layers of cylindrically stacked tubes structure and shilled layers structure, were 3D-printed using the fabricated filaments. The measured compressive properties of the two designs are not significantly different, thus the distribution of stress and resulting strength for both designs are likely to be similar